Study of χc01P→J/ψγ and χb0(1P)→Υ1Sγ Decays via QCD Sum Rules - V. Bashiry (Advances in High Energy Physics)
We present the calculation of the form factor of the χc01P→J/ψγ and χb0(1P)→Υ1Sγ  decays in the frame work of QCD sum rules. We also find branching ratio Brχc01P→J/ψγ = 1.36-0.6+0.9×10-2 which is in agreement with the experimental data. Furthermore, we estimate the Γtot(χb0(1P))=4.2-2.21+3.18 MeV, where experimental bound for full width of χb0 is  Γtot(χb0(1P))<6 MeV.